초등과학수업에서 마인드 맵 활용에 대한 탐색 - 박주현; 문병찬; 송진여; Park, Ju-Hyun; Moon, Byoung-Chan; Song, Jin-Yeo (대한지구과학교육학회지, 2009)
The purpose of this study is to investigate the characteristics of the mind maps which were drawn with pencil or color pens by elementary students. For this study, 31 students of the 6th grade were selected and trained mind mapping. After training, the subjects had drawn mind maps with color pens about the ROCK for 15minutes and drew mind maps with pencil after 2days of mind mapping using color pens. In addition to activities of mind mapping, the students handed in their papers which were written one's impression of drawing two kinds of mind mapping. The results were follows: First, in central circle which was linked words connected firstly with ROCK as key word, the difference of 2kinds mind maps were little showed in the quantity and quality of the words, branches and their adequacy. Second, the mind maps using pencils had more words, branches and images than mind maps of using color pens in the whole assessment. Third, the most students suggested that the mind mapping using pencil were advantage to economy of time, retouching words and branches, also the mind mapping using pencil made the students relax the strain for drawing it because of retouching possibility. Consequently, the results of this study suggest the mind mapping using pencil has advantage effect on the purpose of gaining students' thinking abundantly and economy of time in elementary science classes.